Preliminary species diversity and community phylogenetics of wood-inhabiting basidiomycetous fungi in the Dabie Mountains, Central China reveal unexpected richness - Xiang-Yang Liu; Shi-Liang Liu; Hao-Wen Wei; Xue-Wei Wang; Jia Yu; Shan Shen; Li-Wei Zhou (IMA Fungus)
Abstract Wood-inhabiting fungi have important economic values as well as playing a major ecological role in forest ecosystem cycles. The Dabie Mountains, at the junction of Henan, Hubei, and Anhui Provinces, Central China, provide an ideal climate and favorable niches for the speciation and diversification of various forms of life including fungi. We studied the species diversity and community phylogenetics of wood-inhabiting basidiomycetous fungi that revealed 175 wood-inhabiting basidiomycetous species, of which 20 represented unidentified species, based on morphological and phylogenetic analyses of 575 specimens collected from ten sampling sites. These species belonged to two classes, 11 orders, 42 families, and 106 genera of Basidiomycota, and included 12 edible species, 28 medicinal species, four poisonous species, and seven forest pathogens. Four types of fungal distribution pattern at the genus level were recognized for 65 genera, while another 41 genera could not be placed in any known distribution pattern. The five sampling sites in the eastern part of the Dabie Mountains had significantly higher species diversity and phylogenetic diversity of wood-inhabiting basidiomycetous fungi than those in the western part, and thus deserve priority in terms of conservation. The community of wood-inhabiting basidiomycetous fungi in the Dabie Mountains is generally affected by a combination of habitat filtering and competitive exclusion. This study provides a basis on which to build actions for the comprehensive recognition, utilization, and conservation of wood-inhabiting basidiomycetous fungi in the region.